2012
DOI: 10.1111/j.1365-2389.2012.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter content and features related to associated mineral fractions in an acid, loamy soil

Abstract: Sorption of soil organic matter on mineral surfaces is now recognized as a major organic carbon (C) stabilization process. To investigate the role of organo-mineral interactions in carbon-rich soils, we separated organo-mineral associations by sequential density fractionation in the top- and subsoil of a forest Acrisol (umbrept) from southern France. Fractions were characterized by scanning electron microscopy, X-ray diffraction, elemental analysis, 13C NMR and δ13C. For each horizon, we isolated five types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Therefore, the NOLF and OLF in this study were not composed exclusively of physically uncomplexed organic matter in the sense used by Gregorich et al [30]. The recovery of ~88% of total soil mass in density fractions is similar to Basile-Doelsch et al [16] and Bonnard et al [33], but lower than Swanston et al [34] and Plante et al [35], who recovered ~100% soil mass.…”
Section: Methodological Considerationssupporting
confidence: 57%
“…Therefore, the NOLF and OLF in this study were not composed exclusively of physically uncomplexed organic matter in the sense used by Gregorich et al [30]. The recovery of ~88% of total soil mass in density fractions is similar to Basile-Doelsch et al [16] and Bonnard et al [33], but lower than Swanston et al [34] and Plante et al [35], who recovered ~100% soil mass.…”
Section: Methodological Considerationssupporting
confidence: 57%
“…Similarly, Bonnard et al. () used the multilayer model to explain a general trend of decreasing C/N ratios with increasing δ 13 C ratios in soil fractions of increasing density. Dümig et al.…”
Section: Application Of the Multilayer Model In Soil Science And Relamentioning
confidence: 99%
“…This concept is widely used to explain the marked decrease in the C/N ratios of soil heavy fractions after sonication (Castanha et al, 2008) or to support the enrichment of N in stable OM fractions, i.e., NaOCl-or H 2 O 2 -resistant OM and heavy density fractions (Barbera et al, 2008;Favilli et al, 2008;Zollinger et al, 2013). Similarly, Bonnard et al (2012) used the multilayer model to explain a general trend of decreasing C/N ratios with increasing δ 13 C ratios in soil fractions of increasing density. Dü mig et al (2012) applied the mutilayer model to explain the formation and properties of MOA during pedogenesis.…”
Section: Strong Adsorption Of N-containing Compounds and Enrichment Omentioning
confidence: 99%
“…The organic carbon stabilization process was also studied by Bonnard et al (2012) who analysed organo‐mineral associations using sequential density fractionation in top‐and sub‐soils sampled from a forest in Southern France. All the fractions were characterized by scanning electron microscopy, X‐ray diffraction, elemental analysis, 13 C NMR and 13 C. This specific characterization showed that carbon accumulation in organo‐mineral fractions was similar in both surface and deeper horizons and correlated with a relative enrichment in hydrophobic compounds.…”
Section: Soil Organic Matter and Carbon Interactionsmentioning
confidence: 99%